Prognostic markers in feline hepatic lipidosis: a retrospective study of 71 cats. (11th November 2017) - Kuzi, Sharon; Segev, Gilad; Kedar, Shay; Yas, Einat; Aroch, Itamar
Abstract : Feline hepatic lipidosis (HL) is a common, potentially life‐threatening disease resulting from prolonged anorexia and increased catabolism. This retrospective study included cats diagnosed with HL based on liver cytology or histopathology (years 2004–2015), and aimed to identify clinical and laboratory parameters associated with mortality. The study included 71 cats (47 females and 24 males) and 85 control cats with non‐HL diseases. Most HL cats (90 per cent) were mixed breed, neutered (70; 99 per cent), female (47; 66 per cent), indoor cats (56; 79 per cent), fed dry commercial diets (44 cats; 62 per cent), and with a median age of 7.5 years (range 1.5–16.0). Common primary conditions included gastrointestinal diseases, pancreatitis and cholangiohepatitis (31 cats; 44 per cent) and stressful events (14; 20 per cent). HL was idiopathic in 20 cats (28 per cent). The overall mortality was 38 per cent (27/71 cats). Older age, as well as dullness, weakness, ptyalism, hypoproteinaemia, hypoalbuminaemia, increased serum creatine kinase activity, hypocholesterolaemia and hepatic failure at presentation were significantly (P≤0.033) associated with mortality. The primary disease was unassociated with mortality. Worsening hypoalbuminaemia, hyperammonaemia, hyperbilirubinaemia, electrolyte disorders, and occurrence of cavitary effusions or hypotension during hospitalisation were significantly (P≤0.045) associated with mortality. A decrease of serum β‐hydroxybutyrate during hospitalisation was significantly (P=0.01) associated with survival, likely reflecting improvement in the catabolic state. The identified risk factors may be therapeutic targets.